Batik Culture Revitalization Strategy as a National Identity in the Disruption Era - Al-Razi, Muhammad Fakhruddin; Azhar, Muhammad (Dinamika Kerajinan dan Batik: Majalah Ilmiah, 2024)
Batik is an indigenous Indonesian culture that has been recognized by the world. Apart from being a culture, batik is also the identity of the Indonesian nation because it is a characteristic that distinguishes it from other nations. But along with the times, batik has undergone many societal changes and shifts. This article aims to discuss the shifts that occurred and the challenges of batik as the nation's identity in the era of the Industrial Revolution 4.0. By using qualitative research methods and a literature study approach, this article shows that batik trends in the community have been mixed and even disrupted by contemporary modern trends. The conclusion obtained from this article is the need to revitalize batik as a national identity by digitizing batik to be able to maintain its existence and essence as a national identity in Indonesian society.